Análisis de la recaudación tributaria en el presupuesto fiscal del Estado ecuatoriano, periodo 2013-2017 - Guerrero Proaño, Rommel Erwin (2019)
The tax collection has the purpose of administratively collecting the tax debts of a nation; while the General State Budget is the resources that a country needs to move the economy in a given period of one year. The general objective of the work was to analyze the relationship between tax collection and the fiscal budget of the Ecuadorian State during the 2013-2017 period, using statistical tools. The research methodology that was applied was quantitative, descriptive and correlational, the observation technique was used since official documents of the SRI and Ministry of Economy and Finance of the periods from 2013 to 2017 were reviewed………